Epistemic injustice of the digital divide - Khort, Mikhail; Karimov, Artur; Murtazin, Salavat; Khayaleeva, Adelya (Edelweiss Applied Science and Technology, 2024)
This article examines the problem of the digital divide through the lens of social epistemology, focusing on such aspects as the knowledge gap and epistemic injustice. The authors uses the method of comparative analysis and conceptual analysis to explore the epistemic characteristics of the digital divide and proposes new approaches to overcoming it. The article emphasizes the importance of achieving the UN Sustainable Development Goals related to education and access to knowledge in the hyperinformation age. The originality of the study is that the phenomenon of the digital divide is seen as a knowledge gap. The authors illustrate the digital divide with the example of the problem of equitable access to AI in education and medicine. As a result, the study is not only theoretically significant but also has social implications, stressing the need to bridge the digital divide as a condition for equitable access to information and knowledge for all segments of society.